The influence of jurisdiction size and sale type on municipal bond interest rates: an empirical analysis - Simonsen, Bill; Helgerson, Lee; Robbins, Mark D. (2001)
The authors use data on municipal bond sales in Oregon from 1994 to 1997 to explore whether population (as a proxy for financial-management capacity) and sale type (competitive or negotiated sale) influence interest rates. They find that smaller jurisdictions pay an interest cost penalty in the municipal bond market, and that competitive sales result in significantly lower interest rates compared to negotiated sales. The authors suggest that measures to enhance the financial-management capacity of small governments are warranted and that state laws requiring justification for negotiated sales are appropriate. - Reproduced
Keywords: Municipal bonds; Local finance